Scientific Trajectories in Indian Virology: Innovations, Institutions, and Impact - Dr. V. Basil Hans (International Journal of Vaccines, 2025)
India's substantial research on epidemiology, virology, and public health measures has helped the world understand viral infections better. This article gives an overview of virus research in India, starting with early studies on arboviruses and enteroviruses and going all the way up to current studies on new and re-emerging pathogens including SARS-CoV-2, Nipah, and Zika viruses. Over the decades, India has built a rich legacy in virus research through pioneering laboratory studies, large-scale outbreak investigations, and the establishment of specialized institutes.The National Institute of Virology (NIV), the Indian Council of Medical Research (ICMR), and other major academic centres have been at the forefront of developing advanced diagnostics, creating indigenous vaccines, and setting up surveillance networks across the country. Field epidemiology programs have strengthened early detection and containment, while collaborations with global agencies have expanded access to cutting-edge technology. Advances in genomic sequencing have enabled the rapid tracking of viral mutations, supporting real-time public health responses.The report also talks about the problems that virological research has, such as limited infrastructure and the necessity for scientists from other fields to work together. It also talks about recent progress in genomic monitoring and biotechnology. This paper shows how India's role in worldwide viral research is changing and how ready it is for future pandemics through case studies and policy analysis.
Keywords: Emerging infectious diseases; and India are some of the words that come to mind; epidemiology; public health; viral surveillance; virology